2021
DOI: 10.1007/s40194-020-01055-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flame straightening on the microstructure and mechanical properties of different strength steels

Abstract: In many cases, flame straightening is unavoidable after welding for the reduction of deformation. Due to the not very concentrated heat source, the process can cause significant changes in the microstructure, especially in high strength and wear-resistant steels. Due to their different physical properties, the effects vary depending on the flammable gases (acetylene, propane). The situation is complicated by the fact that the manual technology carries a risk of overheating, which can have detrimental effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Water cooling is even more dangerous as the higher the strength group. Based on practical investigations, Gunnert's method is not recommended as high strength steels fatigue strength improvement process (Gyura et al, 2021).…”
Section: Gunnert's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water cooling is even more dangerous as the higher the strength group. Based on practical investigations, Gunnert's method is not recommended as high strength steels fatigue strength improvement process (Gyura et al, 2021).…”
Section: Gunnert's Methodsmentioning
confidence: 99%
“…The high strength steel spot heating has influence on the microstructure and crack propagation of the welding joints. Researchers (Gyura et al, 2021) found that in high strength steels intentional or accidental heating in the intercritical A 1 -A 3 results in significant damage to the original structure of the smoothed steel and martensite-austenite (M-A) islands causes a significant decrease of toughness, due to the mixed structure formed. The results of the instrumented impact tests have shown that in such case, due to the mixed fabric formed, the crack propagation energy is drastically reduced with nearly unchanged crack initiation energy (Gyura, 2021).…”
Section: Spot Heatingmentioning
confidence: 99%